A novel achromatopsia mouse model resulting from a naturally occurring missense change in Cngb3 - Hassall, M; Barnard, A; Orlans, H; McClements, M; Charbel Issa, P; Aslam, S; Maclaren, R (Association for Research in Vision and Ophthalmology, 2018)
Purpose: A local colony of inbred mice (129S6/SvEvTac origin), in isolation for over a decade, were found to have absent light-adapted electroretinogram (ERG) responses. We investigated the inheritance and genetic basis of this phenotype of cone photoreceptor function loss. Methods: An affected 129S6/SvEvTac colony animal was outcrossed to a C57BL/6J mouse and intercrossed to investigate inheritance in the F2 generation. We performed ERG testing and targeted resequencing on genes of interest (Gnat2, Cnga3, Cngb3, Pde6c, Hcn1, Syne2). The eyes of a subset of animals underwent histologic immunostaining. Results: All 129S6/SvEvTac colony animals tested lacked cone pathway function by ERG testing (n = 12), although rod pathway–based ERG responses remained unaffected. Outcross-intercross breeding showed a recessive inheritance pattern. A novel missense mutation was identified in the Cngb3 gene, which causes an amino acid substitution at a conserved residue (NM_013927)c.692G>A; p.(R231H). The recessive phenotype only affected homozygotes (χ2 = 39, P = 3.2e−10). Cones had normal morphology at postnatal day (PND) 70, but cone cell counts declined from PND 30 to PND 335 (P = 0.038), indicating progressive cone photoreceptor death. Conclusions: We identified the spontaneous occurrence of a 10th model of cone photoreceptor function loss (cpfl10) in an isolated line of inbred mice. Our results indicate that this is caused by a novel missense mutation in the Cngb3 gene, with a fully recessive inheritance pattern. This mouse may provide a more appropriate background against which to assess CNGB3 achromatopsia gene therapy for missense mutations.